1996
DOI: 10.1108/eb013284
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Intergenerational Relations Through Reports of Transfers of Time and Money: A Comparative Study of African‐americans, Hispanics and Whites

Abstract: The purpose of this study was to describe any patterns of distinctive sociocultural adaptation in the form of exchanges of time and money between American households, and to determine whether any observed racial or ethnic differences remain after controlling for social background characteristics. We tested one dimension of the sociocultural adaptation hypothesis — Through processes of distinctive sociocultural adaptation, minority group members learn to survive by adjusting behaviors, values, and informal orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…This assumption is challenged by recent studies that use representative samples of Blacks and Whites to examine the nature and prevalence of kin exchanges of time, money, and other forms of support (Eggebeen and Hogan 1990;Hofferth 1984;Spreitzer et al 1996). The findings vary across studies and by the particular measure of kinship ties, but in general Blacks do not appear to be more involved or generous with their extended family members than Whites.…”
Section: Why Should Kin Matter?mentioning
confidence: 69%
See 2 more Smart Citations
“…This assumption is challenged by recent studies that use representative samples of Blacks and Whites to examine the nature and prevalence of kin exchanges of time, money, and other forms of support (Eggebeen and Hogan 1990;Hofferth 1984;Spreitzer et al 1996). The findings vary across studies and by the particular measure of kinship ties, but in general Blacks do not appear to be more involved or generous with their extended family members than Whites.…”
Section: Why Should Kin Matter?mentioning
confidence: 69%
“…The emphasis on kin support among Black families coupled with the relative silence on this issue in the literature on White families has contributed to the notion that African Americans are unique in their connection to and utilization of kin networks for various kinds of support. This assumption is challenged by recent studies that use representative samples of Blacks and Whites to examine the nature and prevalence of kin exchanges of time, money, and other forms of support (Eggebeen and Hogan 1990;Hofferth 1984;Spreitzer et al 1996). The findings vary across studies and by the particular measure of kinship ties, but in general Blacks do not appear to be more involved or generous with their extended family members than Whites.…”
Section: Why Should Kin Matter?mentioning
confidence: 98%
See 1 more Smart Citation
“…One study even reported that the ethnic difference actually increased with the inclusion of controls for SES (Lee & Aytac, 1998). In contrast, other studies found that ethnic difference became insignificant when SES was taken into account (Burr & Mutchler, 1999; Lee & Aytac; Spreitzer et al, 1996). Much of this research examined women and men together; many studies also combined Mexican Americans with other Latinos/as.…”
Section: Explaining Ethnic Differences In Family Integrationmentioning
confidence: 86%
“…Many studies have examined ethnic differences in some of these types of kin support; their findings did not consistently point to greater integration on the part of either Mexican Americans or Euro Americans. The majority of studies examining financial assistance found that Latinos/as were less likely than Euro Americans to provide it to kin (Eggebeen, 1992; Lee & Aytac, 1998; Spreitzer, Schoeni, & Rao, 1996). And although some scholars found that Latinos/as were less likely to provide emotional support (Spreitzer et al), others found no ethnic difference (Eggebeen) or even a higher prevalence among Mexican Americans (Mindel, 1980).…”
Section: Family Integration: Comparing Mexican Americans and Euro Amementioning
confidence: 99%